2020
DOI: 10.1371/journal.pone.0235852
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes influence medulloblastoma phenotypes and CD133 surface expression

Abstract: The medulloblastoma (MB) microenvironment is diverse, and cell-cell interactions within this milieu is of prime importance. Astrocytes, a major component of the microenvironment, have been shown to impact primary tumor cell phenotypes and metastasis. Based on proximity of MB cells and astrocytes in the brain microenvironment, we investigated whether astrocytes may influence MB cell phenotypes directly. Astrocyte conditioned media (ACM) increased Daoy MB cell invasion, adhesion, and in vivo cellular protrusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Astrocytes are important for normal brain development as well as pathological processes in the central nervous system such as neurodegenerative diseases and brain tumors. Previous studies established that TAs play a critical role in supporting the progression of MB ( Gronseth et al, 2020 ; Liu et al, 2017 ). Our lineage-tracing analyses in this study suggest that TAs in primary MB may migrate from the surrounding brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are important for normal brain development as well as pathological processes in the central nervous system such as neurodegenerative diseases and brain tumors. Previous studies established that TAs play a critical role in supporting the progression of MB ( Gronseth et al, 2020 ; Liu et al, 2017 ). Our lineage-tracing analyses in this study suggest that TAs in primary MB may migrate from the surrounding brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing evidence between wound healing and developing tumors, recent studies are now investigating the complex functions of astrocytes in supporting medulloblastoma growth, as these specialized glial cells are involved in the functional recovery of the central nervous system (CNS) [27,30,31,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Astrocytes are specialized and heterogeneous cells that are essentials to modulate local blood flow as well as to maintain homeostasis of extracellular fluids, ions, and transmitters [59,60].…”
Section: Astrocytes and Medulloblastoma Microenvironment: The New Player Within The Complex Ecosystemmentioning
confidence: 99%
“…The roles of astrocytes in the medulloblastoma microenvironment have been investigated and the studies demonstrated that astrocytes secreted CD133, a key cancer stem cell marker, involved in medulloblastoma tumorigenicity, and alter gene expression, increase invasion and adhesion ofmedulloblastoma cells [58]. Astrocytes can also have direct influence on brain tumor stem cells that are activated by several ligands, including SHH, which enrich the stem cell population.…”
mentioning
confidence: 99%
“…Somatic TERT (telomerase) promoter hotspot mutations are also associated with the SHH subgroup [22,23]. Mutation of PTEN (phosphatase and tensin homolog) is found in more than 5% of human Due to increasing evidence of an association between wound healing and the development of tumors, recent studies have investigated the complex functions of astrocytes involved in the support of medulloblastoma growth, as these specialized glial cells are involved in the functional recovery of the central nervous system (CNS) [29,32,33,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. Astrocytes are specialized and heterogeneous cells that are essential modulators of local blood flow as well as being involved in the maintenance of homeostasis of extracellular fluids, ions, and transmitters [61,62].…”
Section: Molecular Signatures Of Medulloblastoma Tumorigenesismentioning
confidence: 99%
“…The roles of astrocytes in the medulloblastoma microenvironment have been investigated, and studies have demonstrated that astrocytes secrete CD133, a key cancer stem cell marker that is involved in medulloblastoma tumorigenicity and alters gene expression, increasing invasion and adhesion by medulloblastoma cells [60]. Astrocytes can also have a direct influence on brain tumor stem cells that are activated by several ligands, including SHH, which enriches the stem cell population [78].…”
Section: Molecular Signatures Of Medulloblastoma Tumorigenesismentioning
confidence: 99%